Multipart items: proposal for standard and practice - Suja', Balqis ([s.n.], 2006)
This is a proposal for cataloguing of multipart items for the purpose of record sharing and facilitating integration of multipart items record in the National Union Catalogue. This proposal aims at achieving less variation when describing multipart items and to promote more consistent treatment of analytics and parent records. It is also meant to be a guide in an attempt to bring encountered older records in line with current and acceptable practice. Multipart items are a type of series publication -- a monograph that is complete, or intended to be complete in a definite number of finite separate parts. A multipart item is a group of physically separate bibliographic items identified by a common title